Core immovable property vocabulary for European linked land administration - Cagdas, V.; Stubkjaer, E. (TAYLOR & FRANCIS LTD, 2015)
Public information regarding immovable property is recorded in national registries, including cadastre and land registry, building and dwelling (or address) registry, and property tax registry. An efficient land administration system is supposed to orchestrate these registries for cross-border and cross-sector land administration services. The recent developments in Semantic Web technologies and the Linked Data approach provide an efficient and flexible solution for web based integration of datasets recorded in these registries. The mentioned registries were specified according to different data models and standards which lead to interoperability problems. The concerned public organisations therefore need a common data model that clearly identifies the recording units of these registries and their core attributes, as well as relationships between them. The present research responds to this requirement by developing a common vocabulary, a Core Immovable Property Vocabulary, as an extension to the e-Government Core Vocabularies (version 1.0) issued recently by the European Commission (EC). The Core Immovable Property Vocabulary is developed by simplifying and capturing the minimal characteristics of complex domain standards and data specifications, thereby enabling a plain representation of immovable property units and their core attributes that are needed for land administration processes. It thus allows for the publication of land administration data sets within the Resource Description Framework (RDF), and renders the integration of land administration datasets with other registries such as address and civil registries encoded according to the e-Government Core Vocabularies. The vocabulary is the result of an individual research effort, carried out by the authors of the present article, and has recently been hosted by the EC ISA (Interoperability Solutions for European Public Administration) Joinup platform as a semantic asset (see https://joinup.ec.europa.eu/asset/cipv/description). The main contribution is the introduction of the Linked Data approach to the land administration domain which may make land administration data sets more accessible via the Web.
Keywords: Cadastre; Land administration; Linked Data; Linked land administration; e-Government Core Vocabularies; Engineering; Geology; Remote Sensing